Circadian-tunable Perovskite Quantum Dot-based Down-Converted Multi-Package White LED with a Color Fidelity Index over 90 - Yoon, Hee Chang (Sci Rep, 2017)
New metrics of the color and circadian performances of down-converted white light-emitting diodes (DC-WLEDs) are rapidly becoming popular in smart lighting systems. This is due to the increased desire for accurate analytical methods to measure the effects of newly developed quantum dot (QD)-based lighting on the vision, color, and circadian sensors of retina cells in the human eye. In this regard, a two-measure system known as technical memorandum TM-30-2015 (Illuminating Engineering Society of North America), encompassing the color fidelity index (CFI, R (f)) and the color gamut index (CGI, R (g)), has been developed as a new metrics of color to replace the currently utilized color rendering index (CRI, R (a)). In addition, the tunability of the circadian efficacy of radiation (CER) is now more important due to its effect on the control of melatonin suppression/secretion, resetting of the central/local clocks of individuals given their daily cycles, and benefits to human health. In this paper, we developed and analyzed six-colored perovskite (Pe; cyan, green, yellowish green, amber, orange, and red colors) QDs-based multi-package WLED, and optimized the SPDs of tunable PeQD-based multi-package WLEDs in terms of promising human-centric lighting device, given its optimized visual energy, color qualities and health-promoting effects.